AN ANALYSIS OF THE ABILITY OF THE SECOND YEAR STUDENTS OF THE STATE VOCATIONAL HIGH SCHOOL (SMKN) 1 RAMBAH IN COMPREHENDING NARRATIVE TEXTS - Wilma Nasution; Effendy Gultom; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this study is to find out the ability of the second year sudents of the state vocational high school (SMKN) 1 Rambah in comprehending narrative texs. It is a descriptive research carried at from August-September 2018. There are ten classes in this research. The population were 271 students, their characters are homogeneous in terms of academic achievement and age factors. The cluster random strategies technique was choosen due to that every class has equal ooportunity to be a sample group. The sample conpused of two categories, try out class (XI TKJ 1) and sample class (XI AK 1). Try out class consisted of 30 students and 30 students from sample class. In this research, the try out test aimed at acknowledging the validity of the test. The time allocation to administer the try out test and the revised test was 45 minutes for each of them. The data were analyzed by calculating the students’ scores, classified into five level mastery, such as very poor, poor, mediocre, good and excellent. Based on the analyzing data of this research, the students’ ability in comprehending narrative text at the second year students of the state vocational high school (SMKN) 1 Rambah was in good level. Meanwhile, the mean score of the whole students’ scores was 61.93. The implication of the finding is that the second year students of the state vocational high school (SMKN) 1 Rambah is able enough in comprehend narrative texts.Key Words : Students’ Ability, Comprehending Narrative Texts